2016
DOI: 10.1111/flan.12214
|View full text |Cite
|
Sign up to set email alerts
|

Setting Evidence‐Based Language Goals

Abstract: The purpose of this project was to identify target language benchmarks for the German program at Michigan State University (MSU) based on national and international guidelines and previous research, to assess language skills across course levels and class sections in the entire German program, and to adjust the language benchmarks as needed based on the study results and make recommendations for the curriculum. The goal of the study was to identify cost‐ and time‐effective valid and reliable assessment tools f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 25 publications
(28 reference statements)
2
8
0
1
Order By: Relevance
“…Overall, the findings confirm that world language departments need to implement valid and reliable assessment of students’ learning at various points during their program of study and use those data to set benchmarks (Goertler, Kraemer, & Schenker, ). Furthermore, districts could consider supporting data teams (Schildkamp, Poortman, & Handelzalts, ) charged with identifying trends in reading, writing, listening, and speaking data and then rewriting world language curricula to remedy patterns of deficiency, thus promoting positive washback.…”
Section: Discussionsupporting
confidence: 58%
“…Overall, the findings confirm that world language departments need to implement valid and reliable assessment of students’ learning at various points during their program of study and use those data to set benchmarks (Goertler, Kraemer, & Schenker, ). Furthermore, districts could consider supporting data teams (Schildkamp, Poortman, & Handelzalts, ) charged with identifying trends in reading, writing, listening, and speaking data and then rewriting world language curricula to remedy patterns of deficiency, thus promoting positive washback.…”
Section: Discussionsupporting
confidence: 58%
“…Goertler, Kraemer, and Schenker () and Tschirner () summarized the studies undertaken to gauge oral proficiency levels of U.S. college students from their freshman year to graduation (see also Heidrich & Kraemer, , in this issue). These studies showed that the average speaking proficiency level of college students after one year of instruction was NH or IL; after two years, it was IL or IM; after three years, it was IM or IH; and after four years, it was IH without and IH or AL with a study abroad period (see Table ).…”
Section: College Germanmentioning
confidence: 99%
“…Since then, language proficiency focused research has looked at student achievement in high school settings (e.g., Shrum & Glisan, ), while research in higher education has often revolved around proficiency in one modality (e.g., Glisan, Swender, & Surface, ; Swender, ) or in one or two languages (e.g., Magnan, ; Sanders, ). Even though some of this research lacks the breadth of modalities and languages of larger‐scale studies, it still provides insight into proficiency achievement of students since Carroll's study; it has informed many curricular decisions and proficiency target levels throughout the years (see Goertler, Kraemer, & Schenker, , for a summary table of research on level achievement). Additional research related to proficiency focused on how other factors, such as the relationship between anxiety and oral proficiency ratings (see Young, ), impacted student learning.…”
Section: Literature Reviewmentioning
confidence: 99%